Tomato Rab1A homologs as molecular tools for studying Rab geranylgeranyl transferase in plant cells. - Loraine, A E (1996)
Rab proteins attach to membranes along the secretory pathway where they contribute to distinct steps in vesicle-mediated transport. To bind membranes, Rab proteins in fungal and animal cells must be isoprenylated by the enzyme Rab geranylgeranyl transferase (Rab GGTase). We have isolated three tomato (Lycopersicon esculentum, M.) cDNAs (LeRab 1A, B, and C) encoding Rab-like proteins and show here that all three are substrates for a Rab GGTase-like activity in plant cells. The plant enzyme is similar to mammalian Rab GGTase in that the plant activity (a) is enhanced by detergent and (b) is inhibited by mutant Rab lacking a prenylation consensus sequence. LeRab1B contains a rare prenylation target motif and was the best substrate for the plant, but not the yeast, Rab GGTase. LeRab1A, B, and C are functional homologs of the Saccharomyces cerevisiae Rab protein encoded by YPT1 and are differentially expressed in tomato. LeRab1A mRNA, but not that of LeRab1B or C, is induced by ethylene in tomato seedlings and is also upregulated in ripening fruit. The increase in LeRab1A mRNA expression in ripe fruit may be linked to increased synthesis and export of enzymes like polygalacturonase, pectin esterase, and other enzymes important in fruit softening.